Identification of Volleyball Players in Sports Associations in Tirana, Albania - Martiri, Altin; Mema, Blerina (European Journal of Multidisciplinary Studies, 2022)
Anthropometric and physical measurements are necessary to take place every year in age groups differents.The purpose of this study is to identify physical and anthropometric skills between ages in female volleyball players in Tirane,Albania. Methods: Participants in this study were (N=138) volleyball players from three Association Sports; the average age (15-16 yrs.). Measurement for anthropometrics (body weight, body height and waist circumference) and physical abilities T -TEST (Brian mac). Results: Results from ANOVA analysis between three Association Sports show significant differences. Multiple comparisons- LSD post hoc analysis showed results for anthropometrics and also for physical abilities showed different differences between groups of volleyball players.Conclusion: The results show the training process of volleyball players in Association Sports Tirana in Albania is conditioned by the factor available to develop training sessio in with a specific training purpose. There are changes in the agility and speed of the game of volleyball.The results of this study clearly show that the development of female volleyball agility improvement of the se skills scores can be achieved with a specific training model to help players improve their skills.